Um olhar sobre o processo do envelhecimento: a percepção do idoso sobre a velhice em centros de convivência selecionados - Oliveira, Susete Maria Ramos Cortez (2015)
Although it is clear that the number of elderly in Brazil has been increasing, yet little is known about them, and often the authors have spoken by them, giving focus to aging and old age as a negative and homogenizing process. Realizing the need to deconstruct the phenomenon of old age and considers it a social category and culturally constructed, this study sought to understand how the elderly see old age through their perception of the aging process and their personal experience of old age. The research was regional in scope and used a qualitative methodological approach, showing the images and representations of the elderly about aging. The technical procedures used were library research and field research. Data were collected through interviews with one hundred and twenty elderly, aged between 60 and 85 (regardless of gender, social class or race). They were selected in groups of community centers of 2 cities in São Paulo - São Caetano do Sul and Santo André. The social representations were brought back through individual questionnaires consisting of four open and structured questions: a) the meaning of being old; b) how to assess the social acceptance of the elderly; c) how they are perceived in social life; d) what their expectations and desires regarding to the future are. Aiming their subjective view, most of the questions were elaborated to check the perception that older people have of old age - a subjective dimension. The answers were processed qualitatively and quantitatively in a computer by a software, the DSC - Collective Subject Discourse, a method of discourse analysis that allows to reach some social representation. According to the results, there was appreciation of opinions in significant speeches, specially related to the appreciation of themselves and their image, or rather, it was observed manifestations that bring the identity characterizations back through the healthy aging process. The obtained data allowed to point out that, unlike the negative and homogenizing vision of others around the old age, elderly respondents experience the process of aging in different ways and report old age as a stage of pleasure. It was not noticed frustrations, conflicts and any drama in experiencing old age. Also, no feelings of inferiority was identified before changes and losses. It is noticeable and expressed in their speeches, looks and attitudes how different it is if you experience a healthy and active aging process, they speak of motivation to leave home, overcoming depressive states, the improvement of the physical condition, getting implied also the positive reference when they see the condition of being elderly as an important stage of life, mentioning achievements in relation to past generations and the possibility to accomplish the dream of freedom. We can notice that the programs - community centers - show positive responses, however, they need to overcome some barriers to better enable the achievements, participation, autonomy and integration. The programs offer physical, artistic, recreational, educational and leisure activities among others, all of great importance to experience the aging process positively. The issue of integration, however, needs more attention. In a general way, the community centers are legitimated for elderly over sixty and the new Brazilian elderly go far beyond 60. It is important to encourage solidarity between generations without prejudice or barriers. A good society for elderly is a good society for all ages